Factors for Consideration When Setting Prices for Private Healthcare Providers Operating in Public Systems: A Comparison of France and Japan - Ayako Honda; Julie Cartailler; Johann Cailhol; Shinichiro Noda; Zeynep Or (SAGE Publishing, 2023)
Background: Most publicly-funded health systems purchase healthcare from private providers, but the optimal purchasing arrangements between public purchasers and private healthcare providers are yet to be determined. Objective: This study compares the healthcare purchasing arrangements made with private providers in 2 social health insurance (SHI)-based systems to identify factors that influence the prices paid for private healthcare service provision. Results: France and Japan use different approaches to determine the payment arrangements with public and private providers. The presence of for-profit healthcare providers in the French health system explains the different payment rates for public and private healthcare providers in that country. In both France and Japan, in addition to payment rates, several policy tools are used to assure the provision of public good services and the availability of necessary healthcare for all, which public providers are required to deliver but private providers can choose to deliver. Conclusion: This study highlights the importance of considering the profit-making status of the private healthcare providers operating in the healthcare market, and clarity in the roles and responsibilities of the public, for-profit and not-for-profit providers when determining healthcare purchasing arrangements. Regulatory policy instruments, used alongside payment rates, are essential to influence efficiency, equity, and quality in mixed (public-private) health systems.